2019
DOI: 10.1177/1369433218823841
|View full text |Cite
|
Sign up to set email alerts
|

Punching shear resistance of strengthened reinforced concrete interior slab–column connections using ultra-high-performance strain-hardening cementitious composite material

Abstract: The main target of this article is to find out the most applicable strengthening technique to change the brittle punching shear failure of slab–column connection to a ductile one. The considered strengthening technique uses the combined effect of the internal single-leg stirrups and a thin layer of ultra-high-performance strain hardening cementitious composite material provided in either tension or compression side. Thus, 12 slab specimens divided into four groups were prepared and configured. It was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Afefy et al [34] studied the punching shear behavior of RC slabs strengthened with UHPFC and found that by adding a thin layer of UHPFC on the tensile side, the bending performance of the slab was improved as it showed better crack distribution in the tensile side. However, the punching load slightly increased by about 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Afefy et al [34] studied the punching shear behavior of RC slabs strengthened with UHPFC and found that by adding a thin layer of UHPFC on the tensile side, the bending performance of the slab was improved as it showed better crack distribution in the tensile side. However, the punching load slightly increased by about 5%.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of different classes of UHPC materials have been extensively investigated [13]. UHPC has been used in several applications such cast in place grout material in bridge connections [14,15], bridge decks [16], thin slabs [17] and strengthening of existing structures [18][19][20][21]. Meanwhile, limited studies have been conducted on the punching shear behaviour of flat slabs made entirely from UHPC [17,[22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Next is through strengthening the flexural reinforcement leading to an increase of the effective depth of slab, by bonding fiber-reinforced polymer sheeting or casting an upper reinforced concrete layer. [16][17][18][19][20] The third concept is postinstalled shear reinforcement which was first reported by El-Salakawy et al 21 by inserting vertical shear bolts around the column. This method was then studied further by Wörle, 22 Fernández Ruiz et al, 23 and Adetifa and Polak.…”
mentioning
confidence: 99%